Current status of the small hive beetle Aethina tumida in Latin America - Bulacio Cagnolo, Natalia Veronica (2023)
The small hive beetle (SHB), Aethina tumida, is a parasitic pest and scavenger of social bees native to sub-Saharan Africa. It is a generalist species which can also reproduce in association with nests of stingless bees, fruits, and even rotten meat. Although in its native range, it usually does not cause severe damage to strong colonies and nests; it has invaded new areas worldwide, causing significant economic losses to social bees in some locations. Here, we present an overview of the current situation of SHB invasion into Latin America by describing its distribution, its impact on beekeeping and the commercialization of bee products, and its potential risk to native bees. In addition, we discuss the strategies carried out in different countries to manage or prevent its entrance and spread. Our findings highlight the need for further research efforts aimed at filling gaps in our understanding of the dynamics of SHB invasions in Latin America, their sources, and trajectories. By contrasting the experiences in countries in which preemptive and preventive measures were taken with countries in which they were not, we conclude that taking such measures has a positive impact on managing SHB invasions. Late notifications of SHB presence in some countries made it difficult to identify SHB dispersal routes and enabling factors. Interactions of SHB with different honey bee and native bee populations remain under-studied, and research on these interactions will determine the severity of SHB as a pest in the region. Latin America offers a dynamic and diverse environment for studying SHB and its interaction with bees.